Limitations of resting haemodynamics in chronic thromboembolic disease without pulmonary hypertension. Issue 1 (17th January 2019) - Swietlik, Emilia Maria; Ruggiero, Alessandro; Fletcher, Andrew J.; Taboada, Dolores; Knightbridge, Emily; Harlow, Louise; Harvey, Ian; Screaton, Nicholas; Cannon, John E.; Sheares, Karen K.K.; Ng, Choo; Jenkins, David P.; et al.
There is renewed interest in the haemodynamic definitions of pulmonary hypertension (PH), reigniting an old debate about diagnostic thresholds [1]. Recent prospective data support work dating back over 40 years demonstrating patients with "borderline" PH (mean pulmonary artery pressure (mPAP) <25 mmHg) can still have significant morbidity and mortality [2]. Therefore, lowering the mPAP threshold for the diagnosis of precapillary pulmonary arterial hypertension (PAH) has been discussed at World Symposium on Pulmonary Hypertension in Nice, France, in 2018. A potentially different approach has arisen in group 4 (chronic thromboembolic pulmonary hypertension (CTEPH)), where the concept of chronic thromboembolic disease without PH (CTED) has gained traction. Chronic thromboembolic disease (CTED) without pulmonary hypertension is emerging as a new and important disease classification http://ow.ly/ZmK730mv5Xh